Nasal and Fecal Microbiota and Immunoprofiling of Infants With and Without RSV Bronchiolitis - Alba, Claudio; Aparicio, Marina; González-Martínez, Felipe; González-Sánchez, María Isabel; Pérez-Moreno, Jimena; Toledo del Castillo, Blanca; Rodríguez, Juan Miguel; Rodríguez-Fernández, Rosa; Fernández, Leonides (Frontiers in Microbiology, 2021)
Bronchiolitis associated with the respiratory syncytial virus (RSV) is the leading cause of hospitalization among infants aged < 1 year. The main objective of this work was to assess the nasal and fecal microbiota and immune profiles in infants with RSV bronchiolitis, and to compare them with those of healthy infants. For this purpose, a total of 58 infants with RSV-positive bronchiolitis and 17 healthy infants (aged < 18 months) were recruited in this case-control study, which was approved by the Ethics Committee of the Hospital Gregorio Marañón. Nasal and fecal samples were obtained and submitted to bacterial microbiota analysis by 16S rDNA sequencing and to analysis of several immune factors related to inflammatory processes. Nasal samples in which Haemophilus and/or Moraxella accounted for > 20% of the total sequences were exclusively detected among infants of the bronchiolitis group. In this group, the relative abundances of Staphylococcus and Corynebacterium were significantly lower than in nasal samples from the control group while the opposite was observed for those of Haemophilus and Mannheimia. Fecal bacterial microbiota of infants with bronchiolitis was similar to that of healthy infants. Significant differences were obtained between bronchiolitis and control groups for both the frequency of detection and concentration of BAFF/TNFSF13B and sTNF.R1 in nasal samples. The concentration of BAFF/TNFSF13B was also significantly higher in fecal samples from the bronchiolitis group. In conclusion, signatures of RSV-associated bronchiolitis have been found in this study, including dominance of Haemophilus and a high concentration of BAFF/TNFSF13B, IL-8 and sTNF.R1 in nasal samples, and a high fecal concentration of BAFF/TNFSF13B.